Analisis Pendapatan, Biaya Operasional dan Laba Bersih Terhadap Harga Saham - Muhammad Nazriel; Erry Sunarya; Dicky Jhoansyah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
Abstract The tourism industry is one of the fastest growing industries in various countries globally, the tourism industry is an industry that is actively developing, innovating and having a major impact on the country's economy. The tourism sector is also a sector that can trigger economic growth, although often this sector is referred to as a complex sector due to changing tourism trends, this sector is able to move more than 700 million people around the world. However, due to the impact of Covid-19, especially on Tourism, Hospitality and Restaurant subsector companies listed on the IDX, they had to experience a decline in financial performance as evidenced by the decline in share prices of each company in the Tourism, Hospitality and Restaurant subsector. The purpose of this study is to determine the effect of income, operating costs and net profit on stock prices. The methodology used in this study is quantitative methods with a total of 60 samples derived from the financial statements of companies listed on the IDX. The findings in this study were that there was a significant positive effect of earnings on stock prices while operating expenses and net income had no significant effect on stock prices. Keywords: tourism industry; share price; Revenue; Operating Costs; Net Profit